The effect of whole-body vibration as a recovery technique on running kinematics and jumping performance following eccentric exercise to induce delayed-onset muscle soreness - Xanthos, P. D.; Lythgo, N.; Gordon, B. A.; Benson, A. C. (Sports Technology, 2013)
This study investigated the effect of whole-body vibration (WBV) as a recovery modality from delayed-onset muscle soreness (DOMS) compared to a traditional (TRAD) recovery modality. Thirteen recreationally active individuals participated (mean ± SD age, 21.6 ± 3.8 years; body mass, 70.3 ± 10.4 kg). DOMS was elicited via eccentric backward walking on an inclined treadmill for 1 h. Participants were randomly allocated to complete a WBV or TRAD recovery modality first before repeating the treadmill walking and alternate recovery after a minimum 14-day washout period. Recovery was implemented immediately after and at 1, 2, 3 and 4 days post-treadmill walking. Leg soreness and power [squat jump (SJ) and counter-movement jump (CMJ)] were evaluated pre-exercise and at 1, 2, 4 and 7 days post-treadmill walking. Creatine kinase and running patterns, as measured with Vicon 3D analysis, were evaluated pre-exercise and at 2 and 7 days post-exercise. Repeated-measures multivariate analysis of variance with post hoc testing and analysis of variance were used to compare recovery modalities. DOMS was induced, and affected muscle soreness rating, creatine kinase, some jump performances and running gait (p < 0.05). Compared to TRAD, knee flexion during stance and knee extension at take-off were reduced (p < 0.05), whereas hip range of motion increased (p < 0.05) after WBV. As reported previously, eccentric exercise induces DOMS, which affects jump performance and running gait. As some joint kinematics were more significantly affected by WBV compared to a TRAD recovery, it is reasonable to conclude that WBV is not a suitable recovery modality from DOMS.